Degradation of polycyclic aromatic hydrocarbons by ultrasonic irradiation - Park, JK; Hong, SW; Chang, WS (SELPER LTD, PUBLICATIONS DIV, 2000)
Polycyclic aromatic hydrocarbons (PAHs) are known to be hazardous compounds with life threatening effects as some of them are proven to be environmentally obnoxious carcinogenic compounds. Ultrasonic irradiation was investigated as a method of attacking the chemical structure of PAH compounds for a complete breakdown. This method produced very promising results with formation of hydroxyl radical (OH .), which is known as a less selective oxidant and very reactive with carbon-chlorine bonds and carbon-carbon double bonds making them capable of generating aromatic ring cleavage. Ultrasonic irradiation resulted in a decrease of PAHs with time and the dominant free radical reaction became a controlling factor. Further, hydrogen peroxide and argon gas markedly enhanced the degradation efficiency during sonolysis. With these agents, more than 30% of additional degradation efficiencies were achieved for all PAHs used in this experiment. Higher degradation efficiencies of PAHs were observed with lowering organic solvent/water ratios and pH range (acidic condition, pH 2). The apparent kinetics were first-order, with the observed rates ranging from 1.60 to 2.81 x 10(-2) min(-1) depending on types of PAHs and presence/absence of hydrogen peroxide and argon gas.